Cognitive deficits in Parkinson's disease with excessive daytime sleepiness: a systematic review. (1st November 2020) - Jester, Dylan J.; Lee, Soomi; Molinari, Victor; Volicer, Ladislav
Abstract: Objectives: This systematic review synthesizes the most recent literature on neuropsychological deficits in adults with Parkinson's disease who experience excessive daytime sleepiness (EDS). Confounds and methodological limitations are explored. A framework entitled the Cascade Model of Excessive Daytime Sleepiness (CMEDS) is proposed to explain the role of EDS in contributing to cognitive impairment for patients with Parkinson's disease. Method: Systematic search through PubMed, PsychInfo and citation records. In total, 175 articles were screened for possible inclusion. Eight studies were included, encompassing 1373 patients with Parkinson's disease − 442 of whom had Parkinson's disease with EDS. Results: For Parkinson's disease patients with EDS, global deficits, executive dysfunction and deficits in processing speed were found beyond the typical cognitive phenotype of patients without EDS. Language skills, memory and visuospatial skills appeared to be similar between those with and without EDS. In untreated, de novo, patients, there were no cognitive differences between the EDS groups. Conclusion: This review suggests that Parkinson's disease patients suffering from EDS may have additional cognitive deficits globally, in executive control, and in processing speed. As suggested by the CMEDS framework, the impact of EDS on cognition may be related to Parkinson's disease pathology, comorbidities and medication use.